THE RETURN OF SPANISH EMIGRANTS IN EUROPE DURING THE TRANSITION TO DEMOCRACY - Luis Manuel Calvo Salgado; Concha Langa Nuño; Moisés Prieto López (Estudios de Historia de España, 2022)
This text analyses the perception and interpretation of return during the transition to democracy in Spain, from the Spanish political spheres, from the administrative institutions in charge of managing migration policy and from the media. This multiple approach will allow us to better understand how and in what phases a new vision of the phenomenon of emigration and return was developed in this period of recent Spanish history. In order to do so, we will deal, firstly, with the political and administrative decisions that channelled the return, trying to find out to what extent they were effective, but also paying attention to the ideological and legal principles that guided them. Secondly, we will focus on the Spanish print media, which covered both this social phenomenon and the political debates it provoked. To obtain a cross-perspective, we intend to deal, on the one hand, with the written media in general and, on the other, with those specifically designed for emigrants.